(untitled) - Alurkar, S. K. (Singapore, 1997)
Over the last three decades, a spate of solar wind observations have been made with sophisticated ground-based and space-borne instruments. Two highly successful space missions of the Skylab and the twin spacecraft Helios 1 and 2 have amassed an invaluable wealth of information on the large scale structure of the inner heliosphere, the solar and interplanetary magnetic field, coronal holes, interplanetary dust, solar windflows, etc.Solar and interplanetary propagating phenomena have been extensively studied during the last two decades. Very recently, a new simple model based on results from a density-mapping technique, pioneered at Cambridge, UK, has been proposed which overcomes the problems faced by the existing CME-driven shock theories.This monograph puts together those exciting developments in the field of solar and interplanetary dynamic phenomena with their effects, at times hazardous, on the terrestrial environment. It serves as an update and a ready reference for research students and scientists working in this field.
Keywords: Solar wind,Cosmic magnetic fields,Gió mặt trời,Từ trường vũ trụ